2018
DOI: 10.1002/jctb.5592
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene epoxidation over supported silver catalysts – influence of catalyst pretreatment on conversion and selectivity

Abstract: BACKGROUND Ethylene oxide is a key intermediate in the chemical industry. It is produced through catalytic epoxidation of ethylene. Significant economic benefits can be achieved by small improvements in catalyst activity and selectivity. The aim of this work was to study how different preparation methods and pretreatments affect the catalyst performance under industrially relevant reaction conditions. The influence of pretreatment strategy on the selectivity and reaction temperature was for the first time inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…[62] Other reports in the literature have examined the pretreatment of Ag catalysts using CO 2 resulting in shorter induction periods or higher initial selectivity of the catalyst. [63] Based on the findings herein along with prior literature reports, we postulate that a similar phenomenon is occurring in the system reported herein for propylene epoxidation.…”
Section: Competitive Reaction Kinetics Between Co 2 and C 3 H 6 Or Osupporting
confidence: 84%
“…[62] Other reports in the literature have examined the pretreatment of Ag catalysts using CO 2 resulting in shorter induction periods or higher initial selectivity of the catalyst. [63] Based on the findings herein along with prior literature reports, we postulate that a similar phenomenon is occurring in the system reported herein for propylene epoxidation.…”
Section: Competitive Reaction Kinetics Between Co 2 and C 3 H 6 Or Osupporting
confidence: 84%
“…The ethylene pretreatment was carried out in order to remove oxygen adsorbed on the catalyst surface . Aho et al ., however, have recently reported that the most promising thermal pretreatment for ethylene epoxidation was first treating the catalyst with 1 ppm of dichloroethane (DCE) followed by overnight pre‐treatment in 20 vol% ethylene. Nevertheless, all the experiments of the presents study were carried out with the same pretreatment method and confident comparisons between different catalysts performances are still possible.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the optical properties of Ag NPs have been historically exploited in decorative pigments for jewellery/handicrafts, staining glass, or ceramics [ 26 , 27 , 28 , 29 ]. Over the last decades, Ag NPs have found use in many areas, such as catalysis [ 30 , 31 ], optical and electro-optical devices [ 23 , 32 ], surface-enhanced Raman spectroscopy (SERS) [ 33 , 34 ], and antimicrobial agents [ 14 , 35 ]. Ag NPs are promising nanofillers to obtain composites with electrical and optical properties to extend the applicability of SLA including the electronic or biomedical fields [ 13 , 14 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%